Mechanical and thermal properties of low density polyethylene composites filled with dye‐loaded shell powder. Issue 42 (13th July 2016) - Yang, Wenye; Ge, Liuqin; Lv, Han; Xia, Meisheng; Ji, Xiaosheng; Yao, Zhitong
ABSTRACT: To achieve reinforcement and coloring in one combined process of polymer production, a dye‐loaded shell powder (DPSP) based on Congo red and pearl shell powder was prepared and used as a versatile bio‐filler in low‐density polyethylene (LDPE). The DPSP was characterized by means of X‐ray diffraction, Fourier transform infrared spectroscopy and thermogravimetric analysis. The mechanical, thermal, and colorimetric properties of prepared LDPE/DPSP composites were investigated as well. Adding DPSP could significantly increase the strength and stiffness of LDPE composites while giving an outstanding coloring performance. Moreover, the impact strength of LDPE composites was improved at lower filler loading rate, and the maximum incorporation content could reach 10 wt % with a good balance between toughness and stiffness of LDPE composites. The thermal performance studies confirmed an increase in thermal stability and heat resistance of LDPE composites with the incorporation of DPSP. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44118. Abstract :